Recursos e infra-estruturas portuárias : gestão e funcionalidade de um porto : Aveiro (1756-1857) - Amorim, Inês (2014)
Seaports are fundamental infrastructures for the development of commercial relationsbetween the hinterland and the foreland, within the context of maritime economy. A possible way to establish this importance is to evaluate how the seaport policies (local, regional or central management and investments) were responsible for the trade of merchandise between land and sea routes and vice-versa.This issue may be all the more significant if we consider the case of the seaport of Aveiro, located on the Northwest coast of Portugal, subject to diverse localization proposals and finally built far from urban areas (town with a port, which is different from a town within a port). This leads us to reflect on the port management policies from the late 18th century to the early 19th century that could be considered suitable for its construction and consolidation.